PERBANDINGAN ASAM ASETAT DENGAN ASAM FORMIAT SEBAGAI BAHAN PENGGUMPAL LATEKS - Rudi Munzirwan Siregar; Putri Anggita Widodo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Nahdlatul Wathan Mataram, 2021)
Indonesia is one of the largest rubber producers. Almost all garden latex for rubber production must be coagulated before further processing. Research has been carried out on the comparison of acetic acid with formic acid as a latex coagulation agent. This study aims to compare acetic acid with formic acid as a latex coagulation agent. Coconut shell charcoal (particle size 80 mesh) was added to the latex with a weight of 42 grams then the latex was coagulated with acetic acid and formic acid with a pH of 4.7. As a rubber quality research was carried out by measuring the initial plasticity, plasticity retention index and mooney viscosity of rubber. In conclusion, latex coagulated with acetic acid produced better rubber than latex coagulated with formic acid.